Student Resilience After Parental Death - Miftahul Ulva; Sri Putri Rahayu; Desmita Desmita; Rafsel Tasadi (International Journal of Research in Counseling, 2022)
Being a student will not be separated from the learning process and the necessity to complete existing assignments and learning demands. There are many factors that can affect the learning process, including the death of parents. For every child, the death of a parent is not a situation that can be taken for granted, the incident can have both psychological and non-psychological impacts on the child. Not infrequently children can blame themselves, stress to decrease children's learning achievement. This situation that makes children have to survive, is called resilience. Resilience is one of the abilities possessed by a person to survive in difficult situations or suppress. The method used in this study is Descriptive Qualitative. The research subjects in this study were three final-level Islamic Psychology students who experienced the death of one of their parents during college. From the discussion and the results of the researcher's interviews with the three informants, the researchers found that: (1) the ability of students to determine what they want, especially when they feel sad, is to flee to God by means of worship such as prayer, prayer, and prayer, believing in God's destiny, and seeking social support. (2) the student's ability to reveal the emotions of the three informants to allow themselves to cry to express their feelings of sadness, as well as to ask for motivation from the family and the environment. (3) the three informants in the study already had a good future orientation after the death of their parents. Based on the information provided by the three informants, the loss of parents had no effect on their education. Thus, all three informants already have the ability for resilience.